Possible ecologically based ways of preserving and developing the Ukrainian Carpathians - V. І. Nikolaichuk; M. М. Vakerich; M. V. Bilkey; O. P. Chechuy; I. Voloshchuk (Vìsnik Dnìpropetrovsʹkogo Unìversitetu: Serìâ Bìologìâ, Ekologìâ, 2016)
Ukraine has transformed into one of the most environmentally dangerous countries in the world due to the high concentration of industrial production and agriculture and predatory use of natural resources. The current ecological situation in Ukraine is characterized by a deep ecological crisis, which is caused by the laws of operation of the command economy of the former USSR. The majority of the environmental and social indicators of Ukraine are among the worst in Europe. The Carpathian Mountains are among the most significant and interesting landscapes in Europe from the geological and geomorphological, scenic and biological perspectives. The giant arc of the Carpathians begins in southern Romania and passes through Ukraine, Slovakia, Poland, the Czech Republic and Hungary to Austria, crosses all Eastern and Central Europe. A third of the forest reserves of Ukraine are located in the Ukrainian Carpathians, at 53.5% the percentage of forest cover of the area is among the highest in the country. About 50% of the gene pool of Ukraine’s plants, many species of trees and medicinal plants grows there. The geographical location and large area of the rich natural heritage of the Carpathians have multifaceted importance for the conservation of biological, phytocoenotic and landscape diversity and maintaining the ecological balance in the central part of our continent. As with the Alps mountain range, this is an important ecological corridor between Western, Central and Eastern Europe, which promotes the migration of species and their spread into lowland landscapes. In order to preserve biodiversity an inventory of virgin forest ecosystems should be made and strict measures for their protection should be enforced. It is necessary to continue the practice of establishing bilateral areas in cross-border protected areas in order to combine efforts to solve pressing environmental challenges. Conservation of the Carpathians Biodiversity is an urgent problem. Structural changes in the economy of the region are expected to strengthen the recreational value of the Ukrainian Carpathians for the public not only in our country but also in Central and Eastern Europe, reducing the technogenic loading. International cooperation of all countries of the Carpathian region is imperative. The development of tourism in the Carpathians is highly promising, but this should be civilized tourism, taking into account the environmental sustainability of the recreational areas and protected areas.